Reversible median nerve impairment after three weeks of repetitive work - Sorosh Tabatabaeifar; Susanne Wulff Svendsen; Birger Johnsen; Gert-Åke Hansson; Anders Fuglsang-Frederiksen; Poul Frost (Nordic Association of Occupational Safety and Health (NOROSH), 2017)
OBJECTIVES: The aim of this study was to evaluate the development of impaired median nerve function in relation to hand-intensive seasonal work. We hypothesized that at end-season, median nerve conduction would be impaired and then recover within weeks. METHODS: Using nerve conduction studies (NCS), we examined median nerve conduction before, during, and after engaging in 22 days of mink skinning. For a subgroup, we used goniometry and surface electromyography to characterize occupational mechanical exposures. Questionnaire information on symptoms, disability, and lifestyle factors was obtained. RESULTS: The study comprised 11 male mink skinners with normal median nerve conduction at pre-season (mean age 35.7 years, mean number of seasons with skinning 8.9 years). Mink skinning was characterized by a median angle of wrist flexion/extension of 16º extension, a median velocity of wrist flexion/extension of 22 °/s, and force exertions of 11% of maximal voluntary electrical activity. At end-season, mean distal motor latency (DML) had increased 0.41 ms (P<0.001), mean sensory nerve conduction velocity (SNCV) digit 2 had decreased 6.3 m/s (P=0.004), and mean SNCV digit 3 had decreased 6.2 m/s (P=0.01); 9 mink skinners had decreases in nerve conduction, 5 fulfilled electrodiagnostic criteria and 4 fulfilled electrodiagnostic and clinical criteria (a positive Katz hand diagram) for carpal tunnel syndrome (CTS). Three to six weeks post-season, the changes had reverted to normal. Symptom and disability scores showed corresponding changes. CONCLUSIONS: In this natural experiment, impaired median nerve conduction developed during 22 days of repetitive industrial work with moderate wrist postures and limited force exertion. Recovery occurred within 3-6 weeks post-season.